Learning as a modified form of individual experience and its place in distance education - Волков, С. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2020)
The nature of learning in the structure of the educational process is explained by the status of individual’s cognitions, i.e. setting processes, procedures, and methods of acquiring knowledge about the phenomena and regularities of the objective world, and factors that go beyond the generative system, i.e. the set of grammatical, semantic, phonological components of language or mental grammar and mental lexicon. Periodical changes in mental activity leading to changes in behavior and obtaining its result as a certain experience are conditioned by its cyclicality. Learning is a cycle of mental mechanisms of the student: telic state – ideation – communicating – localization. Accordingly, a cycle of mental mechanisms of a teacher is aimed at interaction with the thinking process of a student: centering on the student’s personality and development of his abilities – initiation of imagination, creating its product, i.e. a mental image, idea or concept, developing creative potential – cooperation of interaction – localization of interaction, i.e. adaptation depending on the ethno-psycholinguistic portrait of the student and socio-cultural peculiarities of the educational environment in which the training takes place or which is the object of the training. A cycle can be represented as a reference standard of the cognitive system of an individual, as well as of mental activity, its manifestations, and conditions that provoke “random” phase transitions of consciousness states. A cycle is a series of multilevel factors determining the status of cognitive state in real time and participating in the excitation and acceleration of cognitive functions involved in solving a problem, in particular, the function of interaction with different cognitive systems and the information field represented in communication networks. This function acts as a relative model of oneness, integrity of perception of the problem, and approach to its solution in the process of learning.